(3TQM GdNWH GdfHGJjg (B( (3NWH GHf fHGJg (B)s - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s; (3YHO GdYRjR Hf YKeGf GdbHjUj GdgGTej, CHh GdUbQ,J (B405 (3g` s
(3ChdgG (B:s
(3hHYO aEfc GdJeSJ ai Cf CYdi Ydjc eNJUQkG ai TQM GdNWH GdfHGJjg s
(3BNQgG (B:s
(3eHJhQ hChd GdehLhO ajgG(B: (3jbGd CHGOge EPG GSJCUdge HGdcdjg , hCUdi ai GdHjOGA s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B23 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B121 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B714s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs